The Implementation of The Work Ethics Dynamics at The Police Corps (Exploration Study on Unethical Behavior) - Rahmah, Laily; Himam, Fathul; Riyono, Bagus; Nurcahyo, Arif (Jurnal Ilmiah Peuradeun, 2021)
The work ethics are one of the main determinants of the performance as it is believed to minimize the occurrence of deviant behavior in an organization. The police are bureaucrats who served as law enforcers as well as public servants to maintain security and order, so they are expected to demonstrate ethical behavior to keep the public trust. However, several unethical behavior issues are found in the organization. Cultural organizations in the police are believed to have served as one of the causes of unethical behavior by the police. The effort to build an understanding of the unethical behavior concept as a result of the work ethics implementation that is based on the organizational culture in the police corps through indigenous approaches was set as the goal of this exploratory study. A survey using open questions was given to 82 police staff in one of the regional police in Java. The results of this study illustrated the perspective of the police towards the elements of the work ethics implementation (internalization process, sanctions, and supervision) in the organization that is opening opportunities for unethical behavior. Theoretical and practical implementation of the results of this study would be discussed.